Campur Kode Tuturan Guru Bahasa Indonesia dalam Proses Belajar Mengajar: Studi di SMP Darul Hikam - Prayogi, Akbar; Fatchurrohman, Lutfi; Romadhon, Syahrul; Waningyun, Prissila Prahesta; Kurniawan, Muh Akbar; Abror, Muchlas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The phenomenon of code mixing in the speech of Indonesian teachers during the learning process in the classroom is an interesting topic to study, especially in a bilingual or multilingual environment. This study aims to analyze the mixed forms of code used by teachers, identify the factors that affect their use, and evaluate their impact on student comprehension. Using a qualitative descriptive approach, data was collected through direct observation in the classroom as well as interviews with teachers and students. The results of the study show that the code mix that appears in learning includes three main types, namely mixing code in, mixing code outward, and mixing mixed code. Factors that encourage the use of mixed codes include the limitations of word equivalents in Indonesian, language habits in daily interactions, and pedagogical strategies to facilitate the understanding of teaching materials. Although mixing codes can be an effective tool in explaining certain concepts, their excessive use has the potential to hinder good and correct mastery of the Indonesian language. Therefore, a prudent pedagogical policy is needed in utilizing code mixing to support the effectiveness of learning without reducing students' language competence in formal Indonesian